Community-based initiatives improving critical health literacy: a systematic review and meta-synthesis of qualitative evidence - Liesbeth de Wit; Christine Fenenga; Cinzia Giammarchi; Lucia di Furia; Inge Hutter; Andrea de Winter; Louise Meijering (BMC, 2017)
Abstract Background Critical health literacy enables older adults to make informed health decisions and take actions for the health and wellbeing of themselves and their community, within their own social and cultural context. A community-based approach has the potential to improve the critical health literacy of older adults and their communities. However, it is not clear how such initiatives consider critical health literacy. Therefore, this study explored how community-based initiatives address the critical health literacy of older adults and their communities. Methods A systematic literature search was conducted. Two reviewers independently screened titles and abstracts, as well as the quality of the methodological and community-based elements of the studies. In addition, a meta-synthesis was carried out, consisting of a qualitative text analysis of the results sections of the 23 included studies. Results We identified two main themes, which are practices that contribute to the critical health literacy of older adults as well as their communities: 1) collaborative learning, and 2) social support. In these practices we identified reciprocity as a key characteristic of both co-learning and social support. Conclusions This study provides the first overview of community-based initiatives that implicitly address the critical health literacy of older adults and their community. Our results demonstrate that in the context of one's own life collaborative learning and social support could contribute to people's understanding and ability to judge, sift and use health information. We therefore suggest to add these two practices to the definition of critical health literacy.